Current State of Professional Training of Master Degree Students in Construction Law and Dispute Resolution in Leeds Beckett University - Olha Nahorna (Pedagogical Discourse, 2017)
The author of the article states that arbitration has become one of the primary methods of dispute resolution in the construction industry (which employs a great number of contracts and contractual disputes), thus a formal qualification in this field is highly advantageous both to construction practitioners and construction lawyers.The author describes the current state of professional training of master degree students in Construction Law and Dispute Resolution in Leeds Beckett University, which is aimed at well qualified construction practitioners with an interest in construction contracts and construction disputes resolution. Being distance learning, and delivered via the internet, this master course offers opportunities to people who otherwise would be unable to undertake formal face to face education for different reasons.The aims of the course are to provide an effective, coherent and intellectually challenging postgraduate education in construction law and dispute resolution; to enhance students’ abilities in the identification and evaluation of appropriate decision making strategies; to develop research capability and cognitive skills which enable students to analyse problems in their professional context.The course learning outcomes contribute towards a strong course identity by way of demanding module learning outcomes which are interdependent between the various modules. That is the law modules provide underpinning knowledge for the dispute resolution modules which in turn inform the requirements of the Law and Practice of Claims module.There are regular «live» online lectures and tutorials via Adobe Connect in which students are expected to participate, and there are a number of online discussions on Blackboard. The professional research module is managed through the usual online classes and then by assigning students to individual tutors to supervise the development of the research paper.Thus, elaborated organization of the master course in Construction Law and Dispute Resolution in Leeds Beckett University effectively combines innovative technologies with traditional learning and teaching approaches which equips graduates with all the necessary knowledge and skills to be more efficient at their career path.